Exercise reduces the anxiogenic effects of meta-chlorophenylpiperazine: The role of 5-HT2C receptors in the bed nucleus of the stria terminalis - Fox, James H.; Boucher, Melissa N.; Abedrabbo, Khalil S.; Hare, Brendan D.; Grimmig, Bethany A.; Falls, William A.; Hammack, Sayamwong E. (Frontiers in Synaptic Neuroscience, 2023)
Introduction Two weeks of voluntary exercise in group-housed mice produces a reduction in anxiety-like behaviors across a number of different measures, including a reduction in the anxiety levels typically produced by the anxiogenic serotonergic drug m-chlorophenylpiperazine (mCPP), an agonist at 5-HT2C/2b receptors. We have previously demonstrated that 2-weeks of voluntary exercise blunted the anxiogenic effects of systemic mCPP, and we have also shown that mCPP infused into the bed nucleus of the stria terminalis (BNST) is anxiogenic. Here we follow up on these reports. Methods In Experiment 1 we infused several doses of mCPP into the BNST with or without the 5-HT2C antagonist SB242084. In Experiment 2, we administered mCPP into amygdala subregions and the dorsal hippocampus to investigate site specificity. In Experiment 4 we lesioned the BNST and subsequently infused mCPP systemically, and in Experiment 4 we used RNAscope® to assess BNST 5-HT2C transcripts following wheel running. Results BNST mCPP infusion increased acoustic startle responding, which was by 5-HT2C antagonism, while neither mCPP infused into the amygdala nor hippocampus was anxiogenic. Lesions of the BNST prevented the anxiogenic effect of systemically administered mCPP. Lastly, exercise reduced 5-HT2C transcripts in the BNST. Discussion These results suggest that the BNST is a critical site of action for the effects of exercise on mCPP. Together these data suggest that exercise may reduce 5-HT2C receptor function in the BNST, which may, in part, explain some of the anxiolytic effects associated with wheel running.